Research on Papua, a digital tool with artificial intelligence in favor of learning and linguistic attitudes towards the learning of the English language in students of Spanish language as L1 - Peña-Acuña, Beatriz; Crismán-Pérez, Rafael (Frontiers in Psychology, 2022)
This study examines learners’ perceptions of the linguistic and learning potential of an AI-based English language learning app called Papua. The study took a quasi-experimental approach in which 128 students of the degree in Primary Education at the University of Huelva, Spain, gained experience of using the app over a six-week period, and then answered a questionnaire. This was of a quantitative design, and included the following components: attitudes towards learning English; attitudes towards learning oral and written skills, and towards opportunities for interacting in English; and attitudes towards the motivation provided by the app. These attitudes were contrasted according to the variables memory and self-evaluation. The results of the study showed that oral skills were perceived as the most improved skill. Participants also foregrounded the enhancement of memorization of vocabulary, and positively evaluated the self-evaluation feature included in the app.